PENERAPAN PENDEKATAN PETA KONSEP UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVB SDN 37 PEKANBARU - Lia Susanti; Mahmud Alpusari; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of the problem in this research was the poor students’ achievements in social sciences, it can be seen on students’ social sciences scores. There were 20 of 35 students who had not achieved the Achievement Standard (57.14%), while the ones who achieved were only15 students (42.86%), and the average scores of the class was 66.08. The Achievement Standard that school determines is 77.The method of research was classroom action research implemented in two cycles that consist of planning, action, observation, and reflection. Data were collected by observation technigue, test technigue. The instrument of data collection used observation sheet and test student’s result. At the first meeting in cycle I, the percentage of teachers’ activity was 75% which is categorized as good. At the second meeting, the percentage increased to 75% which is categorized as goodteachers are still not accustomed to using concept maps approach so that teachers do not experience an increase in activity on the second meeting.At the first meeting in cycle I, the percentage increased to 85% that is categorized as good. At the second meeting the percentage increased to 95% which is categorized as very good. The students’ activities had increased. At the first meeting in cycle I, the students’ activities gained 60% which is categorized as less, while at the second meeting in cycle I the students’ activities gained 65% which is categorized asenough.At the firstmeeting of cycle II, the percentage increased to 75% that is categorized as good, while at the second meeting the percentage increased to 95% which is categorized asvery good.The average of students’ achievements before the implementation Approaches to concept Mapwas 66.08 which increased to 78.40 in cycle I, and increased again to 84.23 in cycle II. The result of research showed that implementation Approaches to concept Mapcan improve student’s result of social sciences grade three at SDN37 pekanbaru.Key Words: Study Result, Approaches to concept Map,social sciences